(untitled) (Journal of Economic Research & Business Administration, 2016)
Formation of market economy in Kazakhstan increased interest in forms and methods of tourist services. The development of the industry at an accelerated pace and increase the negative effects of competition and commercialization of tourist activity has led to an understanding of the need for state regulation of tourist business. Within a few generations, a significant part of the population of Kazakhstan used a travel service, resulting in the need for them was the mass, ie, He came back to normal life, became part of the national culture. International tourism is currently one of the most dynamically developing branches of foreign economic activity. The steady growth of the impact of tourism on the world economy as a whole and on the economies of individual countries and regions is one of the most significant, permanent and long-term trends which accompanies the formation and development of the world economy. The tourism industry in the Republic of Kazakhstan on the state level is recognized as one of the priority sectors of the economy. The implementation of the industrial-innovative development of Kazakhstan’s economy leading role belongs to the system of local clusters. Қазақстандағы нарықтық экономиканы қалыптастыру нысандары мен әдістері туристік қызмет көрсету қызығушылығын күшейтті. Туристік бизнесті мемлекеттік реттеу туристік қызметті коммерциялизациялау және бәсекелестік салдарының теріс түсінігінің өсуіне және осы саланың қарқынмен дамуына әкелді. Бірнеше ұрпақтар халықтың едәуір бөлігі Қазақстанның туристік қызметімен тұтынды, соның нәтижесінде оларға қажеттілік болатын бұқаралық, яғни өмір нормасына ұлттық мәдениет бөлігі болып енді. Халықаралық туризм қазіргі уақытта ең серпінді дамып келе жатқан сыртқы экономикалық қызмет салаларының бірі болып табылады. Туризмнің ұдайы өсуіне тұтастай алғанда әлемдік экономиканы, жекелеген елдер экономикасы мен аймақтарын, аса маңызды тұрақты және ұзақ мерзімді үрдістердің, әлемдік шаруашылықтың құрылуы және дамуына толықтай ықпал етеді. Қазақстан Республикасындағы туризм индустриясы мемлекеттік деңгейінде басым экономика саласының бірі болып танылды. Қазақстанның экономиканы дамытудағы индустриялық- инновациялық ережелерін іске асырудағы жетекші рөлі отандық кластерлер жүйесінде атқарылады.